1997
DOI: 10.1155/1997/974282
|View full text |Cite
|
Sign up to set email alerts
|

Keeping an Eye on Crohn’s Disease: Orbital Myositis as the Presenting Symptom

Abstract: Episodic periorbital swelling due to presumed orbital inflammation and myositis caused intermittent apparent proptosis and was the presenting symptom of ileocecal Crohn's disease (CD) in a teenage female with a family history of autoimmune disorders and CD. Orbital myositis, a very rare extraintestinal manifestation of inflammatory bowel disease (IBD), likely represents a process of impaired immunoregulation related to the underlying intestinal inflammation. This rare manifestation of IBD simulates the more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…It is one of the most common orbital disorders, following thyroid associated orbitopathy and lymphoproliferative disease, and accounts for about 5% of orbital disorders [3]. Very rarely it is associated with some systemic diseases such as systemic lupus erythematosus, rheumatoid arthritis, Wegener's granulomatosis, sarcoidosis, scleroderma, polyarteritis nodosa, Kawasaki disease and inflammatory bowel disease (IBD) [7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most common orbital disorders, following thyroid associated orbitopathy and lymphoproliferative disease, and accounts for about 5% of orbital disorders [3]. Very rarely it is associated with some systemic diseases such as systemic lupus erythematosus, rheumatoid arthritis, Wegener's granulomatosis, sarcoidosis, scleroderma, polyarteritis nodosa, Kawasaki disease and inflammatory bowel disease (IBD) [7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study has shown that ocular involvement occurs in 1-2% of patients with IBD [167], with the prevalence of orbital manifestations being presumably lower. Less than 25 cases of IBD associated with orbital inflammation and/or orbital myositis have been reported in the literature [9,[168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183][184][185].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…With regard to treatment, corticosteroids are the mainstay for induction, with some reports employing initial IV pulse dosing (usually 1 mg/kg/day) followed by oral taper and other reports employing only oral dosing, both of which had mixed results [168][169][170]172,[174][175][176][177][178][180][181][182][183][184][185]. Recently, infliximab has been utilized in several patients with refractory IBDassociated orbital inflammation and led to good long-term control [173,179].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Most of the cases of orbital myositis do not have their etiology established 12,27 . Two cases (1.28%) were related to systemic lupus erythematosus 28,29 , one (0.64%) was related to giant cell myocarditis 14 , and another one to Crohn disease 8 suggesting a possible underlying immunologic mechanism 30 . Some authors tend to correlate them to previous infectious process and one case have been shown as a paraneoplasic syndrome 10 .…”
Section: Fig 2 Normal Mri (Second Episode)mentioning
confidence: 99%
“…The most common causes of orbital myositis are: endocrine diseases (in particular Grave's disease) 1 , orbital tumors, connective tissue disorders, infections [2][3][4] , vaccine 5 , cystic lesions 6 , rippling muscle disease 7 and Brown's syndrome, which is characterized by paralysis of the superior oblique muscle, always in an unilateral way but very frequently relapsing. In the past almost every inflammatory process of orbit was classified as a pseudotumor but this term has not been more used so frequently [8][9][10][11][12] . We reviewed 156 cases published in the last 25 years.…”
mentioning
confidence: 99%